Teaching for Transfer to First-Year L2 Writers - Cui, Wenqi (Journal of International Students, 2019)
Previous studies have identified that genres and genre knowledge are not only pivotal for the development of writing expertise but also for facilitating writing-related transfer. However, little research concerns issues of teaching genres for writing transfer to first-year English as a second language (L2) writers at universities in the US. This article attempts to develop a genre-based pedagogic framework for L2 transfer teaching, aiming to help first-year L2 students address linguistic, rhetorical, and genre-bound challenges they confront and improve their writing expertise, as well as develop their ability of writing transfer across disciplines. The goals of this article are dual: (a) to address an existing gap in the literature and research on transfer, and (b) provide academic writing instructions for teaching first-year L2 writers at universities in the United States.